2019
DOI: 10.3847/1538-4357/ab2913
|View full text |Cite
|
Sign up to set email alerts
|

Time Delay Measurement of Mg ii Line in CTS C30.10 with SALT

Abstract: We report 6 yr monitoring of a distant bright quasar CTS C30.10 (z = 0.90052) with the Southern African Large Telescope (SALT). We measured the rest-frame time-lag of 562±2 days between the continuum variations and the response of the Mg II emission line, using the Javelin approach. More conservative approach, based on five different methods, imply the time delay of 564 +109 −71 days. This time delay, combined with other available measurements of Mg II line delay, mostly for lower redshift sources, shows that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
89
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(96 citation statements)
references
References 59 publications
(86 reference statements)
6
89
1
Order By: Relevance
“…In the SWIFT/UVOT grism monitoring of NGC 5548, Cackett et al (2015) showed that the Mg II emission line is not strongly correlated with the continuum variability, and there is no significant lag between the two. However, more recent studies of CTS C30.10 (radio quiet quasar) and 3C 454.3 (blazar) Czerny et al (2019) and Nalewajko et al (2019) show that there are time delays of 562 +116 −68 and ∼600 days, respectively, between the continuum variations and the response of the Mg II emission line. León-Tavares et al (2013) and Isler et al (2013) reported the statistically significant flare-like event in the Mg II emission line in the blazar 3C 454.3.…”
Section: Mg II and Fe Ii Variabilitymentioning
confidence: 98%
“…In the SWIFT/UVOT grism monitoring of NGC 5548, Cackett et al (2015) showed that the Mg II emission line is not strongly correlated with the continuum variability, and there is no significant lag between the two. However, more recent studies of CTS C30.10 (radio quiet quasar) and 3C 454.3 (blazar) Czerny et al (2019) and Nalewajko et al (2019) show that there are time delays of 562 +116 −68 and ∼600 days, respectively, between the continuum variations and the response of the Mg II emission line. León-Tavares et al (2013) and Isler et al (2013) reported the statistically significant flare-like event in the Mg II emission line in the blazar 3C 454.3.…”
Section: Mg II and Fe Ii Variabilitymentioning
confidence: 98%
“…We see that the majority of the sources follow radius-luminosity relation within uncertainties, with CTS252 being an outlier, which could be the hint of the trend of a smaller time-delay for higher Eddington-ratio sources as was already studied for Hβ measurements (Du et al, 2018;Martínez-Aldama et al, 2019a Figure 5. The radius-luminosity relation for MgII broad line using the sources as listed in Table 3 in Czerny et al (2019) and the new measurement of CTS C30.10 (orange star). The red dashed line stands for the standard Bentz relation R Hβ − L 5100 (Bentz et al, 2013), derived for 3000Å using the bolometric corrections from Netzer (2019): log(R BLR /1lt-day) = 1.391 + 0.533 log (L 3000 /10 44 erg s −1 ).…”
Section: Radius-luminosity Relation For Mgiimentioning
confidence: 99%
“…The MgII emission‐line light curve is constructed based on a long‐slit spectroscopy using the SALT telescope in a service mode, using the slit width of 2″; for further details, please read Modzelewska et al () and Czerny et al (). The MgII line information was extracted from the quasar spectra in the wavelength range between 2700 and 2900 Å by fitting different spectral components to the spectra, namely, the power–law component corresponding to the accretion disc emission, FeII‐line pseudocontinuum, and the two kinematic components of MgII line (redshifted and blueshifted Lorentzians), each of which furthermore consists of a doublet at 2,796.35 and 2,803.53 Å, with a doublet ratio of 1.6.…”
Section: Observational Datamentioning
confidence: 99%
“…We show this using the example of a bright quasar CTS C30.10 at z = 0.9, for which the AGN continuum and MgII line‐emission light curves were obtained. The detailed observational analysis was shown in Modzelewska et al () and Czerny et al (). Here, we provide an overview of the time lag determination methods, which provide statistically robust results even for sparse and heterogeneous time series of more distant sources.…”
Section: Introductionmentioning
confidence: 99%